Coastal defence : a study on the performance of Labuan block - Sharifah Nadia, Syed Ahmad (2012)
Coastal defense structure is a structure used as deterrent or breakwater to mitigate erosion that occurred in coastal areas. However, failures often occur on the structure due to problems such as poor installation which does not follow the specifications. Another problem that normally caused the failure of coastal defence structure is the weak bed protection. As such, a case study has been conducted at Pantai Punggur, Johore that uses Labuan Block as coastal defense structure. The Labuan blocks constitute of two concrete block type that are Type B in trapezium shaped and Type A in square shaped. They are suitable to be used in the sandy beach area as wave deterrent. It used geotextile as bed layer. This study aimed to evaluate the effectiveness of Labuan Block at the stated area and factors that resulted in failure for the structure. Two methodologies were applied in this study, first by analyzing the hydrodynamic data such as wave, tide and soil profile to relate with the problem occurred. The second method is by doing visual inspection to get the actual view of the level of erosion and its effect on the study area. From the study, it was found that block height arrangement was not enough to withstand the wave especially during high tide. As a conclusion, suitable height arrangement and improvement on existing bed protection is suggested so that the implementation of Labuan block is more effective and able to last longer.